2020
DOI: 10.3389/fneur.2020.567407
|View full text |Cite
|
Sign up to set email alerts
|

What Does Immunology Have to Do With Normal Brain Development and the Pathophysiology Underlying Tourette Syndrome and Related Neuropsychiatric Disorders?

Abstract: The goal of this article is to review the past decade's literature and provide a critical commentary on the involvement of immunological mechanisms in normal brain development, as well as its role in the pathophysiology of Tourette syndrome, other Chronic tic disorders (CTD), and related neuropsychiatric disorders including Obsessive-compulsive disorder (OCD) and Attention deficit hyperactivity disorder (ADHD). Methods: We conducted a literature search using the Medline/PubMed and EMBASE electronic databases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 244 publications
(269 reference statements)
0
34
0
Order By: Relevance
“…Probiotics are bacteria that help to maintain positive gut health and can also regulate inflammation and immune function. Studies have indicated that TS has been associated with imbalances in the gut microbiota (29). While, children commonly take multivitamins, often to maintain health and prevent deficiencies (14), the effectiveness of these supplements has yet to be investigated addressing symptoms of TS.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are bacteria that help to maintain positive gut health and can also regulate inflammation and immune function. Studies have indicated that TS has been associated with imbalances in the gut microbiota (29). While, children commonly take multivitamins, often to maintain health and prevent deficiencies (14), the effectiveness of these supplements has yet to be investigated addressing symptoms of TS.…”
Section: Discussionmentioning
confidence: 99%
“…Benros and colleagues ( Benros et al, 2014 ) coined the term “Immune activation hypotheses” to account for the evidence that viral and bacterial-induced immune activation during the neurodevelopmental phase is a preeminent inducing factor of vulnerability to psychopathological aberrant behavioral manifestations. Early immune activation could manifest in common features of inhibitory control deficit, including OCD, chronic tics disorders, and Autism Spectrum Disorders (ASD) ( Martino et al, 2020 ).…”
Section: Cytokines and Behavior In Ocd And Asdmentioning
confidence: 99%
“…Inflammation has been extensively discussed in tic pathophysiology. A recent review article on immunological mechanisms in the pathophysiology of tic disorders argues that innate and adaptive systemic immune pathways and neuroinflammatory mechanisms play an important role in the pathogenesis of at least some patients with TS 53 . The article also postulated that hyper-reactive systemic immune pathways and neuroinflammation may help explain the natural fluctuations of tic disorder symptoms over time.…”
Section: Etiologymentioning
confidence: 99%